Plan estratégico de comunicación para elevar la imagen institucional de la secretaría nacional de la gestión de la política, delegación provincial de El Oro, año 2014. - Vásquez Cueva, Gabriela Amarilis (2014)
The development of this thesis entitled Strategic Communication Plan to raise the corporate image of the National Secretary of Policy Management, Provincial Delegation of El Oro, 2014, consisted of a diagnosis -purposing, research work which served to assess the communication problems of the institution and design a solution proposal to strengthen the identity, image, culture and environment of the entity.